Pengaruh Kinerja Keuangan dan Tata Kelola Perusahaan terhadap Penghindaran Pajak - Vianty Adella Santo; , Martha Angelina Manalu; Floretta Angeline (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze the effect of financial performance and corporate governance on tax avoidance, focusing on the relationship between agency theory and corporate tax decisions. Financial performance is measured through Return on Assets (ROA) and Debt to Equity Ratio (DER), while corporate governance is assessed based on board remuneration. The data used in this research consists of information from the financial statements of companies listed on the Indonesia Stock Exchange over a specific period. The results indicate that both ROA and DER do not have a significant effect on tax avoidance. This suggests that financial performance is not always a driving factor in tax avoidance decisions. In contrast, corporate governance has a notable impact on tax avoidance, indicating that companies with good governance practices tend to be more transparent in their financial reporting and avoid risky tax evasion actions. These findings align with agency theory, which posits that conflicts between managers and shareholders can influence corporate decisions. Good governance practices can mitigate such conflicts and promote more ethical behavior in taxation. This research provides important insights for stakeholders to enhance corporate governance in order to minimize tax avoidance and support better tax compliance.